Técnica de realidade virtual para manipulação e deformação de superfícies NURBS - Reis, José Flávio dos (2012)
The Virtual Reality (VR) mainly deals with the creation of three-dimensional environments generated in real time and made available for multisensory interaction with different devices. A high processing capacity and modeling environments is required for applications of this nature. These applications currently extend to various productive sectors such as industry, medicine and health, training (capacity building) and, in particular, in the Education. There are several areas of knowledge that explore VR as a teaching tool to complement the techniques applied to the binomial teaching / learning in a pedagogical context. In recent years, various issues related to the teaching of Mathematics has been a subject of interest and research into the use of Virtual Reality techniques. The developed systems have proved a increase advanced in the use of this technology. One area of the interest for mathematics industry is the study of surfaces NURBS (nonuniform Rational B-Spline). These surfaces have application in many areas of industry and engineer - such as design of automobiles, aircraft, shoes, bottles etc. However, reseachers computer systems were developed as a proposed tool for study and manipulation of NURBS with small levels of interaction and created models. These itens associated with the navigation and involvement, implicit concepts to worked by RV, certainly provide a more natural and user-friendly system. Therefore, this research has come up with a proposal to investigate how VR techniques can be used for teaching and even training in the area of NURBS. Thus, a computer system was developed and evaluated with potential users. The evaluated results demonstrate that virtual reality techniques offer an interesting field of research to provide some computational methods, that lead more dynamic and motivational to study NURBS.